Strategi Public Relations dalam Membangun Brand Image Melalui Instagram Lime Light Bar - Harmia, Dara Ayu Sofie; Setyanto, Yugih (Prologia, 2025)
Lime Light Bar is a new company operating in the food and beverage sector and was founded in 2023 by PT. Untung Sejahtera Makmur, Lime Light Bar offers a Tequila Bar, Nightclub and Lounge concept which is packaged attractively in terms of concept, products, services, and even uploads on social media. If it is related to increasing the brand image of Lime Light Bar in the eyes of the public, then this cannot be separated from the role and function of public relations itself. The image of Lime Light Bar varies according to public perception because this is related to individual assessment. The purpose of this research is to determine the role of public relations in building brand image through Instagram Light Lime Bar. The uniqueness of this bar is its cool atmosphere and different from the others. This research method uses qualitative research methods. This research is research with a qualitative approach. The research was conducted by conducting interviews with Adelwine Rene as Public Relations of Lime Light Bar, Qesya Aliyya, Bramantya Widyanto, Citta Nathania, Salwa Desvitha as customers and Instagram followers @lime.lightbar. The research results found that Lime Light Bar meets a good brand image assessment, namely; (1) Strength of Brand Association (2) Favorability of Brand Association (3) Uniqueness of Brand Association. Lime Light Bar merupakan salah satu perusahaan baru yang bergerak dalam bidang food and beverage dan didirikan tahun 2023 oleh PT. Untung Sejahtera Makmur, Lime Light Bar menawarkan sebuah konsep Tequila Bar, Klub malam, dan Lounge yang dikemas secara atraktif baik secara konsep, produk, pelayanan, hingga unggahan di media sosial. Apabila dikaitkan dengan peningkatan brand image Lime Light Bar di mata masyarakat, maka hal itu tidak terlepas dari peran dan fungsi public relations itu sendiri. Citra Lime Light Bar berbeda-beda menurut persepsi masyarakat karena hal ini berkaitan dengan penilaian secara individu. Tujuan dari penelitian ini adalah untuk mengetahui Peran Public Relations Dalam Membangun Brand Image Melalui Instagram Light Lime Bar. Keunikan dari bar ini adalah suasananya yang keren dan beda dari yang lain. Metode penelitian ini menggunakan metode penelitian kualitatif. Penelitian ini merupakan penelitian dengan pendekatan kualitatif. Penelitian dilakukan dengan melakukan wawancara pada Adelwine Rene selaku Public Relations Lime Light Bar, Qesya Aliyya, Bramantya Widyanto, Citta Nathania, Salwa Desvitha selaku customer dan pengikut instagram @lime.lightbar. Hasil Penelitian menemukan bahwa Lime Light Bar memenuhi penilaian brand image yang baik yaitu; (1) Strength of Brand Association (2) Favorable of Brand Association (3) Uniqueness of Brand Association.